A conceptual study into the potential of Mn+1AXn-phase ceramics for self-healing of crack damage. Issue 1 (January 2015) - Farle, Ann-Sophie; Kwakernaak, Cees; van der Zwaag, Sybrand; Sloof, Willem G.
Abstract Recently, autonomous crack healing has been reported for Ti2AlC and Ti3AlC2 of the Mn+1AXn (MAX) phase ceramics. The desirable healing behaviour is due to the formation of a stable, well-adhering oxide with a high relative volume expansion and having mechanical properties close to those of the matrix. The present analysis aims to predict the occurrence of similar autonomous high-temperature crack-healing behaviour in other MAX phase materials on the basis of postulated primary and secondary criteria analysing their reported thermodynamic, thermo-kinetic and mechanical properties. The analysis correctly identified Ti2AlC and Ti3AlC2 as suitable MAX phase variants for autonomous high-temperature crack healing. Also other Al-containing MAX phases seem promising, of which Ta2AlC and V2AlC were identified as worth a detailed investigation of their crack-healing behaviour. Of the Si-containing MAX phase compounds Ti3SiC2 met the criteria for autonomous high-temperature crack healing.